DFT study of electronic and redox properties of TiO2 supported on olivine for modelling regolith on Moon and Mars conditions. (January 2020) - Escamilla-Roa, Elizabeth; Zorzano, Maria-Paz; Martin-Torres, Javier; Hernández-Laguna, Alfonso; Sainz-Díaz, C. Ignacio
Abstract: Titanium dioxide ( TiO 2 ) is one of the most studied oxides in photocatalysis, due to its electronic structure and its wide variety of applications, such as gas sensors and biomaterials, and especially in methane-reforming catalysis. Titanium dioxide and olivine have been detected both on Mars and our Moon. It has been postulated that on Mars photocatalytic processes may be relevant for atmospheric methane fluctuation, radicals and perchlorate productions etc. However, to date no investigation has been devoted to modelling the properties of TiO2 adsorbed on olivine surface. The goal of this study is to investigate at atomic level with electronic structure calculations based on the Density Functional Theory (DFT), the atomic interactions that take place during the adsorption processes for formation of a TiO regolith. These models are formed with different titanium oxide films adsorbed on olivine (forsterite) surface, one of the most common minerals in Universe, Earth, Mars, cometary and interstellar dust. We propose three regolith models to simulate the principal phases of titanium oxide (TiO, Ti2 O3 and TiO2 ). The models show different adsorption processes i.e. physisorption and chemisorption. Our results suggest that the TiO is the most reactive phase and produces a strong exothermic effect. Besides, we have detailed, from a theoretical point of view, the effect that has the adsorption process in the electronic properties such as electronic density of states (DOS) and oxide reduction process (redox). This theoretical study can be important to understand the formation of new materials that can be used as support in the catalytic processes that occur in the Earth, Mars and Moon. Also, it may be important to interpret the present day photochemistry and interaction of regolith and airborne aerosols in the atmosphere on Mars or to define possible catalytic reactions of the volatiles captured on the Moon regolith. Highlights: Quantum mechanical calculations to simulate TiO2 regolith models. Titanium oxide adsorbed onto (100) forsterite surface. Effect of the adsorption processes in the electronic properties: density of states (DOS) and redox processes. Physisorption and chemisorption to produce regolith models formed with titanium oxide and olivine.